The associations between social environment and adolescents’ psychosomatic health: An ecological perspective - Huang, Yi; Lu, Jinjin; Širůček, Jan (Frontiers in Psychology, 2023)
Objectives It has been known that social environments are associated with adolescents’ health. However, the complex relationship between diverse types of social environments and adolescents’ psychosomatic heath remained unclear. Thus, using an ecological perspective, the current study aimed to examine the associations between social environment and adolescents’ psychosomatic health. Methods We used the data from the Health Behavior in School-aged Children (HBSC) project conducted in the Czech Republic in 2018. A total of 13377 observations were included. Results The region, as a macrosystem, could not explain the variance in adolescents’ psychological and somatic health. The quality of neighborhood environment (exosystem) was significantly related to adolescents’ psychological and somatic health. At the microsystem level, teacher support had stronger, family support had weaker, and peer support had no association with psychological and somatic health. At the mesosystem level, the interactions between family, teacher, and friend support were negligible for adolescents’ psychological and somatic health. Conclusions The results underscore the importance of teachers’ support and neighborhood environment for adolescents’ psychosomatic health. Therefore, the findings suggest the need to improve teacher-adolescent relationships and the neighborhood community quality.